Seleção sexual e comportamento reprodutivo de Mecynogea erythromela (Holmberg 1876) (ARANEAE: ARANEIDAE) - Moura, Rafael Rios (2014)
The formation of couples in nature is dependent on the reproductive strategies adopted by each sex. Typically, the dispute between males for access to partners and mating choice by females are responsible for pairing. The assortative mating may be occur according to different attributes such as color, parasite load, age, aggressive behaviors or size. Although females usually choose their partners, in situations when the costs of reproduction are too high, males might also be very selective. This sexual role reversal is common in species in which males provide parental care to offspring. In the spider Mecynogea erythromela, males invest in parental care. They keep the integrity of the webs, prevent egg sacs to fall on the ground where they can be attacked by ants, and defend their offspring against against predators. Possibly due to this investment in parental care, males are very selective and prefer high quality partners. In some spiders, the quality of females is associated with body size because larger females are more fecund than smaller ones. Additionally, larger males win most disputes against smaller males and, thus, have advantages in access to high quality partners. These behaviors explain the occurrence of size assortative mating in M. erythromela. In this study, I investigated, in the first chapter, the care offered by males, the effect of care on offspring survival and the evolution of paternal care in this spider. In the second chapter, I analyzed male choice, the relation between female size and fecundity and the result of the intrasexual competition among males on the formation of positive size assortative mating in M. erythromela.